Analysis of behind the armor ballistic trauma. (May 2015) - Wen, Yaoke; Xu, Cheng; Wang, Shu; Batra, R.C.
Abstract: The impact response of body armor composed of a ceramic plate with an ultrahigh molecular weight polyethylene (UHMWPE) fiber-reinforced composite and layers of UHMWPE fibers shielding a block of ballistic gelatin has been experimentally and numerically analyzed. It is a surrogate model for studying injuries to human torso caused by a bullet striking body protection armor placed on a person. Photographs taken with a high speed camera are used to determine deformations of the armor and the gelatin. The maximum depth of the temporary cavity formed in the ballistic gelatin and the peak pressure 40 mm behind the center of the gelatin front face contacting the armor are found to be, respectively, 34 mm and 15 MPa. The Johnson–Holmquist material model has been used to simulate deformations and failure of the ceramic. The UHMWPE fiber–reinforced composite and the UHMWPE fiber layers are modeled as linear elastic orthotropic materials. The gelatin is modeled as a strain-rate dependent hyperelastic material. Values of material parameters are taken from the open literature. The computed evolution of the temporary cavity formed in the gelatin is found to qualitatively agree with that seen in experiments. Furthermore, the computed time histories of the average pressure at four points in the gelatin agree with the corresponding experimentally measured ones. The maximum pressure at a point and the depth of the temporary cavity formed in the gelatin can be taken as measures of the severity of the bodily injury caused by the impact; e.g. see the United States National Institute of Justice standard 0101.06-Ballistic Resistance of Body Armor. Graphical abstract: Cavity profiles formed in the gelatin. Highlights: Experimental characterization of temporary cavity formed in gelatin. Mathematical/computational models of behind the armor trauma. Time histories of pressure induced in the gelatin.